Culture and resource management for subsistence: An anthropological perspective - Timseena, Bhanu (Occasional Papers in Sociology and Anthropology, 2008)
DOI: 10.3126/opsa.v2i0.1066 Occasional Papers in Sociology and Anthropology Vol.2 1990 p.40-47